2018
DOI: 10.1155/2018/6056948
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Silymarin and Silibinin against DNA Damage in Human Blood Cells

Abstract: Silymarin (SM), a standardized extract derived from Silybum marianum (L.) Gaertn, is primarily composed of flavonolignans, with silibinin (SB) as its major active constituent. The present study aimed to evaluate the antigenotoxic activities of SM and SB using the alkaline comet assay in whole blood cells and to assess their effects on the expression of genes associated with carcinogenesis and chemopreventive processes. Different concentrations of SM or SB (1.0, 2.5, 5.0, and 7.5 mg/ml) were used in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In the study of Togay et al [100], DNA damage in rats with streptozotocin-induced diabetes symptoms were decreased after silibinin treatment. Similarly, Fernandes Veloso Borges et al [101] showed that silibinin (5.2-15.5 mM) reduced the amount of DNA in the comet tail compared to positive control. Silibinin is known to exhibit strong antioxidant activities and its protective effects against ROS have been demonstrated in different cell lines [41,42].…”
Section: Protective Effects Of Silibinin Against Mycotoxin Genotoxicitymentioning
confidence: 85%
“…In the study of Togay et al [100], DNA damage in rats with streptozotocin-induced diabetes symptoms were decreased after silibinin treatment. Similarly, Fernandes Veloso Borges et al [101] showed that silibinin (5.2-15.5 mM) reduced the amount of DNA in the comet tail compared to positive control. Silibinin is known to exhibit strong antioxidant activities and its protective effects against ROS have been demonstrated in different cell lines [41,42].…”
Section: Protective Effects Of Silibinin Against Mycotoxin Genotoxicitymentioning
confidence: 85%
“…Instead, at their physiological nontoxic concentrations, they maintain nucleophilic tonus by a mechanism called “para-hormesis” leading to the activation of the transcription of the antioxidant enzymes, which leads to protection and activation of repair mechanisms [33]. This type of silymarin action was reported; specifically the ability to prevent DNA damage in human blood cells [34] or to increase the antioxidant enzyme transcription in animals [35].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CP administration caused a reduction in Bcl-2 level which is improved by SMN and MZN administration. As it upregulates the expression of Bcl-2, SMN has antigenotoxic properties and modulates the expression of genes involved in cell defense against DNA damage 29 .…”
Section: Discussionmentioning
confidence: 99%